Anatomical characteristics, microfibril angle and micromechanical properties of cottonwood (Populus deltoides) and its hybrids. (October 2016) - Wang, Yurong; Liu, Cangwei; Zhao, Rongjun; McCord, Jessica; Rials, Tim; Wang, Siqun
Abstract: Samples were prepared using stem xylem from cottonwood ( Populus deltoides ) and two cottonwood hybrids ( P. deltoides  ×  Populus maximowiczii and P. deltoides  ×  Populus trichocarpa ), which grew in Tennessee, United States. The anatomical characteristics, microfibril angle, and mechanical properties of the cell wall in juvenile wood (two-year-old) were investigated by means of microscopy image analysis system, X-ray diffraction, and nanoindentation (NI). The results showed that the double-wall thickness of the fiber cells in the hybrid poplars was thicker than that of the pure poplar, and the ratio of wall to lumen of fiber cell (0.40) of the P. deltoides  ×  P. trichocarpa, which had the slowest growth rate, reached the greatest value among the three poplar clones. Their microfibril angles (MFA) of the cell wall in the investigated samples ranged between 11.5° and 16.7°, and they correlated positively with growth rates of the three poplar clones. The average hardness and reduced elastic modulus were 0.25 GPa and 8.58 GPa for P. deltoides, 0.28 GPa and 8.34 GPa for P. deltoides  ×  P. maximowiczii, and 0.31 GPa and 12.2 GPa for P. deltoides  ×  P. trichocarpa, respectively. P. deltoides  ×  P. trichocarpa with the slowest growth rate had the greatest micromechanical values among the three poplar clones. In combination with growth characteristics of the three poplar clones, the findings of the analyses on their wood properties provided information-rich data that not only could describe juvenile wood properties but also could be used in selective breeding for the three poplar clones in Tennessee, USA. Highlights: The pure poplar and its hybrids from the same male parent were firstly compared in biomass quantity and quality. The double-wall thicknesses of the fiber cells in the hybrid poplars were thicker than that of the pure poplar. The micromechanics value was largest in Populus deltoides  ×  Populus trichocarpa with the slowest growth rate. The microfibril angle and hardness in Populus deltoides  ×  Populus maximowiczii were larger than that of Populus deltoids .